The Effect Of Strategic Management Accounting, Tax Knowledge And Competitive Advantage On Tax Compliance Through Organizational Performance As Intervening Variables - Dhaniel Hutagalung; Yvone Augustine (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
To examine and explain the implementation of strategic management accounting, tax knowledge and competitive advantage on tax compliance mediated by organizational performance.The data collected in this study are primary data. Primary data collection was carried out by survey method using a research instrument in the form of a questionnaire. This research was conducted at companies in Jakarta, Bogor, Depok, Tangerang, Serang. The sample units are business entities and individual business actors whose scope is manufacturing. The unit of analysis is companies in Jakarta, Bogor, Depok, Tangerang, Serang, while the respondents are staff, general managers, CEOs or company owners. Data analysis used inferential statistics from partial least squares (PLS).The findings in this study indicate that strategic management accounting, tax knowledge and organizational performance have a significant direct relationship to tax compliance. While competitive advantage has no effect on tax compliance, however, it has an indirect effect through organizational performance. Thus, competitive advantage has a positive and significant effect on tax compliance mediated by organizational performance. Then strategic management accounting does not have a direct and significant influence on organizational performance. In addition, organizational performance was found not to have a mediator role, both from strategic management accounting and tax knowledge on tax compliance.The authenticity of this research is evident from the effort to include tax compliance which is indicated by an increase in the amount of tax paid to the state treasury every year in proportion to the amount of income. Therefore, in this study, a question instrument was developed related to the effect of increasing tax payments on tax compliance itself.